(untitled) - Rogers, John (Harlow, 2006)
The practice file includes two sections: Language work (grammar,vocabulary and writing,including selections which follow the format of the BEC; and talk business.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Business english,Study and teaching,Tiếng Anh thương mại,Học và dạy